A study of the barriers of implementation of accounting information system: Case of listed companies in Tehran Stock Exchange - Salehi, Mahdi (Journal of Economics and Behavioral Studies, 2011)
Accounting information system is one of subsystems in management information system that is very important in all companies. The current study reviews barriers in implementation by postulating six hypotheses of accounting information system (middle managers, human resources, organizational structure, environmental factors, financial issues, and organizational culture) in companies listed on Tehran Stock Exchange. Finally, some results were obtained in this manner: barrier of organizational structure with 26 percent, middle managers with 26 percent, human resources with 25 percent, environmental factors with 21 percent, organizational culture with 19 percent and finally financial issues with16 percent were identified as barriers factors influencing on the establishment of accounting information systems in listed companies on Tehran Stock Exchange. Generally to eliminate these barriers, management, financial managers and staff must be trained practically by experienced teachers in accounting information systems to use the specialist and professional managers, to lengthen position of managers, to clear financial issues, to inform benefits of system establishment to company’s managers. By giving reward to managers and staff try to encourage these people to use the new system. To justify staff that the establishment of new system would be their advantages; by the lever of reward, to encourage staff to compete in learning and work with the system in staff and learn to compete with systems that can accelerate performing and implementing the system.